(untitled) (The Pretoria Student Law Review, 2021)
‘Oppression’ can take a great number of forms, depending on its context, purpose and subjects. The forms of oppression which are the subject of this article are racial prejudice and patriarchy. These two forms of oppression are relevant here to the extent that they are imposed on Black women. Within this context, the struggle of Black women is twofold, in that it is comprised of the Black person’s struggle, against racial prejudice, as well as the woman’s struggle, against patriarchy. Additionally, this struggle, against racial prejudice and patriarchy, is also twofold in the sense that it exists in society and is also condoned by the law. Therefore, the racial prejudice will be discussed as it relates to the Blackness of Black women and the patriarchal prejudice will be discussed as it relates to the ‘womanness’ of Black women. This paper, then, recalls the racial and patriarchal oppression of the Black woman by looking at the said oppressions as they have existed in society as well as some ways in which the law has aided or reinforced them. Once the oppressions, their existence and legal enforcement, have been outlined, this paper then visits the topic of music as a documentation of and escape from the experience of these oppressions by Black women. It should also be noted that, due to similarities which will be outlined in the article, the focus of this paper is squarely on the experience of the Black woman in the United States of America (USA) and South Africa. Therefore, some racially prejudicial laws will be sampled from these countries. Furthermore, some music by Black female artists from both countries will be sampled too. Above all, this article is presented as a reminder of sorts that the law does not exist in a vacuum — it applies to, has consequences for and is experienced by people.